Developmental evolution facilitates rapid adaptation. Issue 1 (December 2017) - Lin, Hui; Kazlauskas, Romas; Travisano, Michael
Abstract Developmental evolution has frequently been identified as a mode for rapid adaptation, but direct observations of the selective benefits and associated mechanisms of developmental evolution are necessarily challenging to obtain. Here we show rapid evolution of greatly increased rates of dispersal by developmental changes when populations experience stringent selection. Replicate populations of the filamentous fungusTrichoderma citrinoviride underwent 85 serial transfers, under conditions initially favoring growth but not dispersal.T. citrinoviride populations shifted away from multicellular growth toward increased dispersal by producing one thousand times more single-celled asexual conidial spores, three times sooner than the ancestral genotype. Conidia of selected lines also germinated fifty percent faster. Gene expression changed substantially between the ancestral and selected fungi, especially for spore production and growth, demonstrating rapid evolution of tight regulatory control for down-regulation of growth and up-regulation of conidia production between 18 and 24 hours of growth. These changes involved both developmentally fixed and plastic changes in gene expression, showing that complex developmental changes can serve as a mechanism for rapid adaptation.